Banking Supervision and COVID-19: A Handbook - Lackhoff, Klaus (Verlag C.H.BECK Recht - Wirtschaft - Steuern, 2021)
Lackhoff Banking Supervision and COVID-19 The COVID-19 pandemic is the first crisis with which the Single Supervisory Mechanism has to cope. This mechanism was only established in response to the financial crisis. While it is not yet clear which ramifications the pandemic will have for the financial sector, regulators and in particular super visors have taken swift measures to enable credit institutions from the prudential perspective to deal with the situation. The measures already adopted lay also the ground for future legislative and supervisory responses to the dynamic development of the pandemic and touch upon general legal issues of the SSM. The book brings together the perspective of the European and national supervisors and the perspective of the supervised entities. In the first two parts the adopted measures at the Union level (e.g. in respect of dividends and IFRS 9) and the national level in France, Germany, Italy and Spain are described. The third and fourth part provide the supervised entities’ perspective to these measures and look at upcoming challenges (e.g. recapitalisation and remuneration issues).